Peran Pemangku Adat Suku Tengger dalam Menjalankan Sistem Hukum Adat - Fatmawati Fatmawati (Fakultas Hukum Universitas Islam Jember, 2016)
Advances in science and technology has led to erosion of the values of the authenticity of the Indonesian nation, known as the number of local wisdom. Indigenous peoples Tengger Wonokitri Village is a village where people are obedient to the positive law in Indonesia as well as keep the Law of indigenous patrimony. They were led by a Shaman or customary holders who chaired the Tengger community as a big family led social life, maintain and protect the lives of law to run it properly. Chairman of the joint indigenous people routinely hold salvation always known by the village or ceremonial